A new species of Phragmipedium (Orchidaceae: Cypripedioideae) from Peru - Parizaca, Alexander Damian; Díaz-Morales, Melissa; Pupulin, Franco (Phytotaxa, 2019)
A new species of Phragmipedium section Lorifolia, P. cabrejosii, is described and illustrated from Peru, and its affinities are discussed. It is mainly compared with P. caricinum, from which it is distinguished by the simple inflorescence, the elliptic dorsal sepal, that is apically white, the shorter, apically twisted pale yellow petals tinged with rose, and the ovate-subrhombic staminodial shield (vs. reniform).